2020
DOI: 10.3174/ajnr.a6428
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Radiation Dose and Scanning Time While Preserving Diagnostic Yield: A Comparison of Battery-Powered and Manual Bone Biopsy Systems

Abstract: BACKGROUND AND PURPOSE:There is scarcity of data on the comparative efficacy between bone biopsy drill systems across various types of bone lesions. Our aim was to investigate differences in diagnostic yield, scanning time, and radiation dose between manual and battery-powered bone biopsy systems in CT-guided biopsies of lytic, sclerotic, and infectious bone lesions. MATERIALS AND METHODS:This was a retrospective single-center institutional review board-approved study. A total of 585 CT-guided core needle biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…Comparable to the results of Cohen et al, our study demonstrated that procedural duration of all evaluated anatomical locations was slightly lower with the powered drill biopsy system, although this time saving was not significant [4]. Although the powered drill approach is reported to offer shorter scanning time for biopsies of densely sclerotic lesions in addition to less specimen artifacts [10,18], no significant difference in procedural duration between biopsies of osteolytic and osteoblastic lesions was observed in our study. Aside from considerations related to radiation exposure and duration, many factors influence the choice of a bone biopsy system such as availability, costs and operator preference [10].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Comparable to the results of Cohen et al, our study demonstrated that procedural duration of all evaluated anatomical locations was slightly lower with the powered drill biopsy system, although this time saving was not significant [4]. Although the powered drill approach is reported to offer shorter scanning time for biopsies of densely sclerotic lesions in addition to less specimen artifacts [10,18], no significant difference in procedural duration between biopsies of osteolytic and osteoblastic lesions was observed in our study. Aside from considerations related to radiation exposure and duration, many factors influence the choice of a bone biopsy system such as availability, costs and operator preference [10].…”
Section: Discussionsupporting
confidence: 66%
“…Although the powered drill approach is reported to offer shorter scanning time for biopsies of densely sclerotic lesions in addition to less specimen artifacts [10,18], no significant difference in procedural duration between biopsies of osteolytic and osteoblastic lesions was observed in our study. Aside from considerations related to radiation exposure and duration, many factors influence the choice of a bone biopsy system such as availability, costs and operator preference [10]. Therefore, not only do local preferences differ with respect to biopsy systems and procedures, but also the radiation exposures of CT examinations can vary significantly by institution [20,21].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The biopsy was technically difficult, due to increased bone density, and was non-diagnostic as the core samples taken were found to contain compacted bone fragments only. Biopsies of sclerotic bone lesions performed using similar equipment have been reported in the literature to have a diagnostic yield of between 55.9% and 82.7%[ 1 , 2 ]. A subsequent surgical biopsy was considered, however, it was felt that on balance the bone lesions were most likely to be prostate cancer metastases despite the unusual presentation and a further biopsy was not pursued.…”
Section: Imaging Findingsmentioning
confidence: 99%
“…Minimally invasive, percutaneous image-guided biopsy techniques have become the preferred method for obtaining representative samples from bone lesions [1]. In recent years, a device for battery-powered drill-assisted bone tissue harvesting was introduced as a valuable alternative to conventional manual drilling [2][3][4]. Advantages of this battery-powered drill device include higher rotation speed with shorter intervention time, easier application and the possibility to collect larger core samples with less patient discomfort [3].…”
Section: Introductionmentioning
confidence: 99%